EFFECTS OF BOARDROOM TUSSLE ON STOCK RETURN OF MALAYSIAN LISTED COMPANIES - Tee, Peck-Ling; AIK, Nai-Chiek; Khong, Yeen-Lai (Journal of Contemporary Issues and Thought, 2018)
Due to differences in opinions and goals, disagreement within the board of directors is common in corporate world. Conflicts in the boardrooms can occur not just between groups of shareholders trying to acquire controlling interest in a company, but also between executive and non-executive directors who represent different stakeholders. Reputation damaging effects model predicts that boardroom tussle events have negative influence on stock returns, whilst the concentration of ownership and control that followed after the tussles can reduce agency problem and positively influence stock returns. This research includes all the 30 events of boardroom tussles involving 10 public listed companies over the period from year 2014 to year 2017 that are announced in Bursa Malaysia website as the sample. This research applies paired-sample compare means ttest method with hypothesized mean difference value of zero to determine whether cumulative abnormal return (CAR) is significant over various event windows for boardroom tussles. Results show that CAR is generally positive before the announcement, but become negative thereafter. In addition, CAR of affected companies is significantly negative over the period of five trading days after the event, indicating that the Malaysian stock market might not be semi-strong form efficient. Stock traders can utilise public information on boardroom tussle to sell the shares of affected company and purchase back five trading days later to earn an abnormal profit.